Spiritualism in Sri Krishna‟s Flute and Sufi Poet Mohammad Jalaluddin Rumi - Chadha, Sonia; Mishra, Parul (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
avyāja-mañjula-mukhāmbuja-mugdha-bhāvair āsvādyamāna-nija-venu-vinoda-nādam | ākrīdatāmaruna-pāda-sarojruhābhyām ārdremadīya-hrdayebhuvanārdramojah ||15|| (Thakura, 2017) Indian land is considered as abundance dignified folk lore through its rich traditions and culture. Music is in its soil that generates sweet melody that has its own unique embellishment. Nevertheless the land is known for its monuments, rivers, capes, Himalayas but music connects all part in one single thread crossing all boundaries of nation along with spiritualism. The ambition of this paper is to dig out the connectivity through the Lore of Indian Mythos and Sufism of Rumi. The flute is a common musical instrument which is the part of our Lord Krishna prayer while Rumi‘s flute or reed a poem that glorify the process of its separation as soulful instrument. Lord Krishna being the avatar of Vishnu is known for his flute and its melodious music contain the philosophy of this universe whereas Muhammad Jalaluddin Rumi world greatest Sufi poet also composed a song on the basic philosophy of reed and its hollow part. The divine love and its pain is hidden in this reed attract the world towards its. The flute of Northern Indian tradition lore is associated with Lord Krishna while Rumi‘s reed portrays his agony, grief, desire and tears. Hence forth the same instrument presents two value systems of our life and constructed a new part of ethicality.